Covid-19 and the Health Economic-Industrial Complex: structural fragilities and possibilities of facing the sanitary crisis - Sabbatini, Rodrigo; Fonseca, Camila Veneo Campos (Cadernos do Desenvolvimento, 2023)
The aim of this study is to discuss the global dynamics of the production and innovation system of the Health Economic-Industrial Complex (HEIC), especially how structural fragilities have been made evident due to the emergence of COVID-19 pandemic. Drawing on this discussion, the paper intends to present an introductory reflection, though propositional, regarding measures that can stimulate internalization, development and utilization of some technologies included in the concept of “Revolution 4.0” not only as part of a socio- economic development project, but also as a way to fight the sanitary emergency.